Blue (Balaenoptera musculus) and fin (B. physalus) whale vocalisations measured from northern latitudes of the Atlantic Ocean - Boisseau , O.; Gillespie , D.; Leaper, R.; Moscrop, A. (J. Cetacean Res. Manage., 2023)
Vocalisations were recorded in the vicinity of sighted blue whales (Balaenoptera musculus) and fin whales (B. physalus) in the North Atlantic between Iceland and Greenland in August 2004 from a hydrophone towed behind a research vessel and from free floating sonobuoys. The structures of recorded calls were broadly similar to those reported from other areas, but lacked the stereotypical patterning of those signals thought to represent reproductive displays. Counts of non-patterned blue whale calls indicated low vocalisation rates, with a mean of 0.62 phrases per whale per hour (0.12 A-B and 0.49 arch phrases per whale per hour). However, vocalisations were highly clustered in time, with 80% of blue whale calls ascribed to the focal animals arriving within a single 80 second period. It is not clear what behavioural, geographical or seasonal trends may influence the vocalisation rate of large baleen whales, and thus direct comparisons between areas are difficult. However, it is hoped the results presented will be of use in interpreting remote recordings of blue whales made from the North Atlantic. Hydrophones were also monitored continuously over 7,757km of trackline using an automated detection algorithm developed for North Atlantic right whales (Eubalaena glacialis). However, no North Atlantic right whales were seen or heard during the study period.